THE PRACTICAL ASPECT OF ERGONOMICS IN HINDU RELIGIOUS CEREMONY IN BALI - Sutjana, D P; Adiputra, Nyoman (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES; Vol. 2, No. 1 Maret 2008)
The word of ergonomics is not found in Balinese vocabulary. In fact, the Balinese are very proud to work with comfortable-, and fitted tools in all sectors of their daily live activities, including in the religious ceremony. Therefore, it is hypothesized, that the Balinese applying the ergonomics principles for their better performances. To test the stated hypothesis, a study was carried out. Participatory observation technique was applied. It is followed by interview to the respondents, and also associated with documentation to the subject studied. Subject studied were the offerings made in conducting religious ceremony, the temporary building for cremation of the dead body, and the temple building. The results found are as the followings: a) the temporary building for religious ceremony is made based on the anthropometrics measurements of the user, such as upper reach, side reach, knee height, buttock height, shoulder height and should width; b) the forms and sizes of offerings are adjusted according to the place provided; c) the container for an offering has been improved from time to time for efficiency and made of locally produced raw materials; d) the size of offering container is made based on the hand sizes such as grip, width of the hand and counted in traditional unit; e) the interior design, for room or temple building is made fit for it?s appropriate function. Therefore, it is concluded that in doing their daily live activities related to religious ceremony, ergonomics principles are applied. Comfortability, easy to use, and feeling of satisfaction are the criteria in using any kind of tools for Balinese. It is suggested that more research is needed to explore more data on the application of ergonomics in Balinese daily live.
Keywords: ergonomics aspect, Hindu religious eremony, Balinese